EVALUATION OF CERTAIN INSECTICIDE MOLECULES AGAINST CHILLI POD BORER, Spodoptera litura IN ANDHRA PRADESH - P. VIJAYALAKSHMI (The Journal of Research ANGRAU, 2016)
Field experiments were conducted during 2010 -11 and 2011- 12 at Horticultural Research Station, Lam, Guntur to evaluate the new insecticides for the management of chilli pod borer, Spodoptera litura. Among the eleven insecticides tested in 2010-11, Spinosad 45 SC @125 ml ha-1 (23.16) recorded lowest pod borer damage followed by Emamectin Benzoate @200 g ha-1 (24.31) and Novaluran 10 EC @ 375 ml ha -1(27.61). In 2010-11, Spinosad 45 SC @125 ml ha-1(4.16), Emamectin Benzoate@ 200 g ha-1 (4.52) were found to be significantly superior in reducing the pod borer damage. With respect to yield (q ha-1), Spinosad 45 SC @125ml ha-1sprayed plot recorded highest yield (33.57 q ha-1) followed by Emamectin Benzoate@200 g ha-1 (29.06 qha-1), Novaluran 10 EC@375 ml ha-1 (28.96 q ha-1) and Lufenuron @500 (27.96 q ha-1) in 2010-11 where as in 2011-12,Spinosad 45 SC @125 ml ha-1(32.93 q ha-1) treated plot recorded highest yield than other insecticides. Based on the overall efficacy of insecticides over two years, Spinosad 45 SC @125 ml ha-1proved as most effective insecticide in controlling pod borer infesting chilli.